Assessment of emergency awareness and preparedness among students and employees at Benguet State University – Buguias Campus - Viloria, Zheynie P.; Moyao, Warren G. (Technium Social Sciences Journal, 2026)
In the Philippines, ranked the world’s most disaster-prone nation, recent calamities like Typhoon Carina (2024) inflicted ₱308.5 million in school damages, underscoring the urgent need for robust emergency preparedness in hazard-vulnerable higher education institutions (HEIs) such as Benguet State University–Buguias Campus (BSU-Buguias), a landslide hotspot in the Cordillera.​ This mixed-methods study assessed awareness levels among students and employees for earthquakes, fires, typhoons, and landslides; evaluated overall emergency preparedness; and identified institutional gaps to bolster DRRM resilience. An explanatory sequential design surveyed 291 respondents (268 students, 23 employees) using a reliable (Cronbach’s α=0.943) 4-point Likert-scale questionnaire, followed by key informant interviews. Data were analyzed via weighted means, standard deviations, and thematic analysis, grounded in Situational Awareness, Protection Motivation, and Organizational Preparedness Theories. Overall awareness was "Aware" (M=3.09), highest for earthquakes (3.33, Completely Aware) but lowest for landslides (2.87); preparedness was moderately "Aware" (M=2.57), with high willingness (3.20) offset by low supply accessibility (1.96) and training (1.98). Employees showed greater variability; qualitative data highlighted signage and route deficiencies.​ Findings reveal a critical awareness-preparedness disconnect, urging hands-on drills, accessible supplies, hazard-specific signage, and LGU partnerships to translate motivation into operational resilience, aligning with RA 10121 mandates for safer Philippine HEIs.